IMPLEMENTASI PRINSIP AKUNTANSI SYARIAH PADA UMKM BAKPIA JOYA: ANALISIS KEADILAN, TRANSPARANSI, DAN MASLAHAH - Ani Pujiati (Jurnal Akuntansi dan Bisnis, 2025)
This study focuses on evaluating the application of Islamic accounting concepts within the operations of the Bakpia Joya MSME, situated in Adijaya Village, Pekalongan Sub-district, East Lampung Regency. The research adopts a descriptive qualitative methodology. Data gathering involved the triangulation of methods: in-depth interviews, direct observation, and document review (documentation). The analytical framework employed is the Sharia accounting principle, which stresses fundamental values such as justice (‘adl), transparency (al-amanah), and general utility (maslahah). The research findings suggest that the Bakpia Joya MSME has already integrated several Sharia accounting tenets into its practices. This is most notably seen in its policy of an equitable and fair wage system, the presence of simple and open financial recording, and social involvement or positive contribution to the local environment. Nevertheless, this implementation remains informal and has not been fully standardized according to the provisions in the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Based on these results, there is a crucial implication that Sharia-based MSMEs must strengthen their financial management. This reinforcement aims to boost business accountability and viability (sustainability).